MentalEaseKit - Davenport, Zoe (East Carolina University, 2023)
MentalEaseKit is a business built on the idea of providing college students with a possible solution to mental health disparities. Our solution is to provide students with a “tool kit” that will provide them not only with tangible products to help them destress but also resources for students to use when or if they need them.
Keywords: mental health; business; entrepreneur; group project; honors